Age at Breast Cancer Diagnosis in Populations of African and European Ancestry. Issue 2 (March 2014) - Kadhel, Philippe; Multigner, Luc
Abstract Based on US national cancer registry data, age differences at breast cancer diagnosis have been reported between African‐American women and European‐American women. Such differences between populations of African and European ancestry have not been studied in other countries at a nationwide level. Here, we report and compare descriptive nationwide epidemiological indicators of invasive breast cancer for the populations of European ancestry living in the US and in mainland France and for women of African ancestry living in the US and in the French West Indies (Martinique and Guadeloupe). Based on the available data, we determined age frequency distributions, world age‐standardized incidence, and the distribution of expected cases of breast cancer in a standard population of women by age. The age frequency distributions revealed that women of African ancestry were younger at diagnosis than women of European ancestry. By contrast, compared with the US regardless of ancestry and mainland France, the standardized incidences appeared lower, and the largest numbers of expected cases younger, in the French West Indies. The populations with African ancestry were not homogeneous in terms of epidemiologic indicators of age‐related breast cancer. These descriptive findings suggest that populations of African ancestry cannot be considered uniform when determining whether it would be appropriate to decrease the age of entry into screening programs for breast cancer.